The Security of Nato’s Eastern Flank Following Decisions Made at the Allied Summit in Vilnius - Marek Kulczycki; Marek Musioł (Politeja)
The unfolding events since 2014, particularly regarding the aggressive foreign policy and military activities of the Russian Federation in Ukraine, have led to a  deterioration in the state of international security. Consequently, the North Atlantic Alliance (NATO) found itself in a new situation that required a response and decisive action. The recent NATO summits have played a crucial role in shaping security policy and guiding strategic decisions for member states, notably in enhancing the security of NATO’s eastern flank. The primary research question addressed in this article is the extent to which the 2023 summit in Vilnius will genuinely contribute to improving security on NATO’s eastern flank. The significant military commitments made during the summit also carried a symbolic dimension. The article aims to analyse and evaluate the decisions taken by NATO at the Vilnius summit, utilising research techniques and methods such as interviews, the Delphi method and scenario analysis. The central thesis posited in the article is that NATO’s reaction, a consequence of decisions made during the Vilnius summit, will be crucial for strengthening the security of NATO’s eastern flank and the development of the Alliance’s military capabilities. To achieve this objective, the article will present selected scenarios for the development of the situation based on insights obtained from experts during interviews. Undoubtedly, the findings of this article will be an invaluable resource for the academic community, professionals, individuals in the security sector and policymakers in the political sphere.